Serum sCD95L concentration in patients with spinal cord injury. (April 2015) - Biglari, Bahram; Büchler, Axel; Swing, Tyler; Child, Christopher; Biehl, Elisabeth; Reitzel, Tim; Bruckner, Tom; Ferbert, Thomas; Korff, Sebastian; Rief, Harald; Gerner, Hans-Jürgen; Moghaddam, Arash
Objective: To determine serum concentrations of soluble CD95 ligand (sCD95L) in patients with traumatic spinal cord injury. Methods: Patients with traumatic spinal cord injury were recruited. Blood was collected on admission to hospital and at 4 h, 9 h, 12 h, 24 h, 3 days, 7 days, and 2, 4, 8 and 12 weeks postadmission. Serum concentrations of sCD95L were determined via immunoassay. Result: The study included 23 patients. Mean sCD95L concentrations were significantly lower at 4 h, 9 h, 12 h and 24 h than at admission, and were significantly higher at 8 and 12 weeks, compared with admission. Conclusion: The serum sCD95L concentration fell significantly during the first 24 h after traumatic spinal cord injury. Concentrations then rose, becoming significantly higher than admission levels at 8 weeks. sCD95L may represent a possible therapeutic target for traumatic spinal cord injury.